The Tripusat Education Strategy in Improving the Quality of Elementary School Education in Aceh Besar District - Mukhlisuddin Ilyas; Musriadi Musriadi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Promoting educational quality demands collaborative involvement among stakeholders outside traditional schooling. The Tripusat concept—comprising school, home, and community—embodies an integrated educational framework that fosters students’ cognitive, social, and character development. This study investigates the effect of Tripusat in improving the quality of elementary education and identifies implementation strategies in primary schools within Aceh Besar Regency. A qualitative method utilising a naturalistic phenomenological design was employed to investigate participants' actual experiences and perceptions of collaborative educational activities. Data were gathered via observations, interviews, and documentation including school principals, educators, parents, and community members. The results indicate that successful collaboration across schools, families, and communities substantially enhances student learning outcomes, fortifies character development, and fosters supportive learning environments. However, obstacles persist, such as insufficient parental engagement, coordination issues, and limitations in institutional capacity, which impede the effective execution of joint initiatives. The study emphasises the necessity of fortifying communication channels, cultivating institutional collaborations, and augmenting stakeholder engagement to optimise the execution of Tripusat. This research presents both conceptual and practical insights for enhancing educational quality via collaborative governance in primary education, along with policy-relevant recommendations for bolstering stakeholder engagement in school-based educational development.